Public transport use among the urban and rural elderly in China: Effects of personal, attitudinal, household, social-environment and built-environment factors - Yi Zhang (Journal of Transport and Land Use, 2018)
Public transport brings significant benefits to the aging society by providing essential mobility to the elderly. However, few studies have investigated the factors that impact public transport use among the urban or rural elderly. This study explored the effects of personal, attitudinal, household, social environment, and built environment factors on the public transport trips of the elderly. The research data was collected from 274 urban and rural neighborhoods of Zhongshan, a medium-sized Chinese city. The negative binomial regression models suggest that, all else being equal, living in a neighborhood with a high level of public transport service, abundant green space along walking routes connecting home and bus-stops, or a relatively balanced structure of age or income is strongly connected to more public transport trips of the elderly. The results also indicate that a strong preference for public transport is significantly related to the public transport use among the elderly. These findings facilitate our understanding of the correlates of public transport use while providing insights into achieving an effective design of policies to encourage public transport use among the elderly in China.